PENDEKATAN MATEMATIKA DALAM KIMIA - Devia Hervina; Nurul Hasanah (CV. ADIBA AISHA AMIRA, 2024)
Mathematics plays an important role in the development of chemistry, such as to improve understanding, prediction, and modeling a chemical phenomenon more accurately. This article discusses how the mathematical approach in chemistry. Using the library research method, namely collecting data from various sources such as books, articles, and previous research. Several mathematical approaches were found, such as group theory, linear equations, transformation geometry, and operations in mathematics, the mathematical approaches used are equations to calculate chemical parameters, such as operations between compounds, simple descriptions of relationships between compounds, equilibrium, and symmetry operations.